Lost youth in the global city: class, culture and the urban imaginary - Dillabough, Jo-Anne (Critical youth studies, 2010)
Theoretical "breaks" and youth cultural studies : post-industrial moments, conceptual dilemmas, and urban scales of spatial change -- Spatial landscapes of ethnographic inquiry phenomenology, moral entrepeneurship, and the investigation of cultural meaning -- Lost youth and post-industrial urban landscapes : researching the interface of youth imaginaries, and urbanization -- Warehousing "ginos", "thugs" and "gangstas" in urban Canadian schools : gender rivalries and subcultural defenses in late modernity -- Urban imaginaries and geographies of emotion : ambivalence, anxiety, and class fantasies of home -- Impossible citizens in the global metropolis : race, landscapes of power, and the new "emotional geographies" of the city -- Legitimacy, risk, and belonging in the global city : neo-liberalism, individualization, and the language of citizenship